PECULIARITIES OF THE IMMUNOLOGICAL BODY REACTION AT HBV-INFECTION - Tymkovich, M.A.; Maliy, V.P.; Lyadova, T.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
As e result of the conducted immunological researches the dynamics of the pro-inflammatory and contra-inflammatory cytokines synthesis in the pacients with acute and chronic HBV infection was studied and on the basis of their analysis the types of immunological body reaction at HBV were established: normally reactive, dissociative, hyporeactive and hyperreactive. The got results allow to recommend the necessity of complex investigation of patients with acute viral hepatitis B with determination of markers of active viral replikation (DNA HBV) and level of principal regulators cytokine.